2022
DOI: 10.1177/11297298221095320
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of right atrial bypass grafting in the management of central venous occlusive disease in patients undergoing hemodialysis

Abstract: Introduction: Central venous occlusive disease (CVOD) is a complication that can occur in patients with end-stage renal disease who are receiving hemodialysis. When CVOD develops, patients often require multiple re-interventions to maintain their dialysis access. CVOD can be treated by various strategies such as balloon angioplasty, stenting, lower limb or extra-anatomical grafts, hybrid grafts or surgical bypasses such as right atrial (RA). In this systematic review, we aim to evaluate the indications, techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“… 17 Limited long-term outcome data are available at present regarding open SVC reconstruction for HD-dependent patients. Paik et al 18 recently reported the first systematic review of 55 dialysis patients who underwent right atrial bypass grafting for central venous occlusion. They reported a 30-day mortality of 4% after right atrial bypass construction.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Limited long-term outcome data are available at present regarding open SVC reconstruction for HD-dependent patients. Paik et al 18 recently reported the first systematic review of 55 dialysis patients who underwent right atrial bypass grafting for central venous occlusion. They reported a 30-day mortality of 4% after right atrial bypass construction.…”
Section: Discussionmentioning
confidence: 99%